Hyperbranched polymers as non-viral vectors for gene delivery - Alazzo, Ali (2018)
The successful clinical translation of non-viral gene delivery systems has yet to be achieved due to the biological and technical obstacles to preparing a safe, potent and cost-effective vector. Hyperbranched polymers have emerged as promising candidates to address gene delivery barriers owing to their relatively simple synthesis and ease of modification compared to other polymers, which makes them more feasible for scale up and manufacturing. In the first part of this thesis, we compare hyperbranched poly(amino acids) synthesised by co-polymerising histidine and lysine, with hyperbranched polylysine prepared using the well-known ‘ultra-facile’ thermal polycondensation route, to investigate the effects of histidine units on the structure and gene delivery applications of the resultant materials. The conditions of polymerisation were optimised to afford water-soluble hyperbranched polylysine-co-histidine of three different molar ratios with molecular masses varying from 13-30 kDa. Spectroscopic, rheological and thermal analysis indicated that the incorporation of histidine modulated the structure of hyperbranched polylysine to produce a more dendritic polymer with less flexible branches. Experiments to probe gene delivery to A549 and H1299 cells, surprisingly, indicated that the co-polymers containing histidine were not more effective in transfecting a luciferase gene than hyperbranched polylysines synthesised as established literature comparators. We attribute the variations in gene delivery efficacy to the changes induced in polymer architecture by the branching points at histidine residues, and obtain structure-function information relating histidine content with polymer Tg, pKa and ability to form stable polyplexes with plasmid DNA. These results are of significance to nanomedicine design as they indicate that addition of histidine as a co-monomer in the synthetic route to hyperbranched polymers changes not only the buffering capacity of the polymer but has significant effects on the overall structure, architecture and gene delivery efficacy. It has become known that many cationic polymers are cytotoxic and although a large number of polycations have now designed to address the toxicity problem, there is still a practical need to develop a fast and reliable method for assessing the safety of these materials. In this regard, metabolomics provides a high throughput and comprehensive method that can assess the potential toxicity at the cellular and molecular level. Therefore, in the second part of this thesis, metabolomics was applied to investigate the impact of hyperbranched polylysine, hyperbranched polylysine-co-histidine and branched polyethylenimine polyplexes, on the metabolic pathways of A459 and H1299 cell lines. The study revealed that the polyplexes downregulated metabolites associated with glycolysis and the TCA cycle, and induced oxidative stress in both cell lines. The fold changes of the metabolites indicated that the polyplexes of polyethylenimine and hyperbranched polylysine affected the metabolism much more than the polyplexes of hyperbranched polylysine-co-histidine. This was in line with transfection results, suggesting a correlation between the toxicity and transfection efficiency of these polyplexes. This part highlights the importance of metabolomics approaches not just to assess the potential toxicity of polyplexes but also to understand the molecular mechanisms underlying their action, which could help to design more efficient vectors. In the third part of this thesis, we investigated the ability of the hyperbranched polymers to condense and deliver siRNA. The results indicated that the higher molecular mass polymers achieved better siRNA delivery and gene silencing than the lower molecular mass form of the polymers and the lysine-only polymer was more efficient than the histidinylated one. These results can be attributed to the low charge (molecular mass) and stiffness of siRNA molecules in comparison with plasmid DNA, which in combination with the impact of histidine incorporation on the structure of the hyperbranched polymers can also explain the lower efficiency of histidinylated polymers. Overall, this thesis is highlighted the impacts of structural factors on the gene delivery applications of hyperbranched polymers and the importance of these factors to inform the design of new polymeric vectors. Also, metabolomics approaches were introduced to this area, not only to evaluate the safety of gene vectors but also to understand the molecular basis by which these vectors act. The data together suggest that the hyperbranched polymers prepared during thermal polycondensation of amino acids have some efficacy in preliminary gene delivery applications, and that these might be improved with future studies to be a candidate for clinical purposes.